2021
DOI: 10.3390/sym13040628
|View full text |Cite
|
Sign up to set email alerts
|

Unconventional SUSY and Conventional Physics: A Pedagogical Review

Abstract: In supersymmetric extensions of the Standard Model, the observed particles come in fermion–boson pairs necessary for the realization of supersymmetry (SUSY). In spite of the expected abundance of super-partners for all the known particles, not a single supersymmetric pair has been reported to date. Although a hypothetical SUSY breaking mechanism, operating at high energy inaccessible to current experiments cannot be ruled out, this reduces SUSY’s predictive power and it is unclear whether SUSY, in its standard… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 41 publications
0
11
0
Order By: Relevance
“…On the one hand, replacing (24) in (20), taking the covariant derivative and using the Bianchi identity (25) we get…”
Section: Susy In the Adjoint Representationmentioning
confidence: 99%
See 1 more Smart Citation
“…On the one hand, replacing (24) in (20), taking the covariant derivative and using the Bianchi identity (25) we get…”
Section: Susy In the Adjoint Representationmentioning
confidence: 99%
“…The composite field e a γ a ψ are fermonic one-forms and they are killed by the spin 3/2 projector. Such embedding of spin 1/2 fields in the adjoint representation of the superalgebra is the so called 'unconventional supersymmetry' [20,21,22,23,24,25,26]. In 2+1 dimensions the action is based on the Chern-Simons term and in [27] the authors showed that the only propagating local degrees of freedom are the fermions.…”
Section: Introductionmentioning
confidence: 99%
“…Extensions of these ideas to four dimensions can be found in [23,32]. In unconventional supersymmetry (for a review see [33]) a spin-1/2 field is introduced directly in the supersymmetry gauge connection, not as a fundamental gravitino field but combined with the vielbein in the form,…”
Section: The Matter Ansatzmentioning
confidence: 99%
“…In unconventional supersymmetry (for a review see [26]) a spin-1/2 field is introduced directly in the supersymmetry gauge connection, not as a fundamental gravitino field but combined with the vielbein in the form,…”
Section: The Matter Ansatzmentioning
confidence: 99%